2019
DOI: 10.3389/fpls.2019.00465
|View full text |Cite
|
Sign up to set email alerts
|

The DOF-Domain Transcription Factor ZmDOF36 Positively Regulates Starch Synthesis in Transgenic Maize

Abstract: Starch synthesis is a complex process that influences crop yield and grain quality in maize. Many key enzymes have been identified in starch biosynthesis; however, the regulatory mechanisms have not been fully elucidated. In this study, we identified a DOF family gene, ZmDOF36 , through transcriptome sequencing analysis. Real-time PCR indicated that ZmDOF36 was highly expressed in maize endosperm, with lower expression in leaves and tassels. ZmDOF36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 56 publications
(63 reference statements)
1
38
1
Order By: Relevance
“…In cereals, Dof genes play a role in seed protein accumulation and mobilisation [ 60 , 77 , 78 ]. In maize, ZmDof36 and ZmDof3 play a role in seed starch accumulation [ 79 , 80 ]. However, for B. napus, the accumulation of oil in the seeds is of economic importance.…”
Section: Discussionmentioning
confidence: 99%
“…In cereals, Dof genes play a role in seed protein accumulation and mobilisation [ 60 , 77 , 78 ]. In maize, ZmDof36 and ZmDof3 play a role in seed starch accumulation [ 79 , 80 ]. However, for B. napus, the accumulation of oil in the seeds is of economic importance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ZmDof3 was found to be exclusively expressed in the endosperm of maize kernel and participate in the regulation of starch accumulation and aleurone development in maize endosperm (Qi et al, 2017). Another maize Dof gene ZmDof36 was also reported to be highly expressed in maize endosperm and function in starch synthesis by regulating the expression of starch synthesis genes (Wu et al, 2019). In this study, ClDof2, ClDof5, ClDof8, ClDof21 and ClDof35 showed much higher expression in leaves than in other tissues, suggesting that they play essential roles in leaf development.…”
Section: Discussionmentioning
confidence: 99%
“…Type I starch synthesis genes is negatively associated with APETALA2/ethylene-responsive element binding protein family transcription factor encoded by Rice Starch Regulator1 (RSR1) (Fu and Xue 2010). RSR1 gene over-expression suppressed the starch production genes, whereas in rsr1 mutants the amylose content was increased (Wei et al, 2017;Wu et al, 2019). Furthermore, RSR1 regulates seed size; yield isolated and characterized the genes controlling pericarp color, nutritional quality, storage time and rice fragrance.…”
Section: Genetic Of Grain Qualitymentioning
confidence: 99%
“…The toxins are only useful to identify the presence of certain classes of G proteins in an extract (Ying et al, 2018). GTP binding proteins which are not substrates for the toxin catalyzed ADP ribosylations (Wu et al, 2019). Immunoblot method using antisera against peptides from known G proteins have also been very powerful (Hsing et al, 2007).…”
Section: Detection Of Gtp-binding Proteinsmentioning
confidence: 99%